Georgia Architectural and Historic Properties Survey of 912 Nardo St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 912 Nardo St., Valdosta, Ga., December 1980. 2 houses that are 1 story rectangular shiplap sided with gabled tin roof and exposed rafters. Gabled porch. Interior chimney. Set on brick piers. Double hung sash windows with 6/6 and 2/2 lights. Poor condition. Date of Construction: App. 1920-1930. Typical houses of this neighborhood. Not significant in terms of a N.R. district. Too many houses have been torn down and there are too many modern intrusions.
Georgia Architectural and Historic Properties Survey of 912 Nardo St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.8 MB (82,633,792 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)